2021
DOI: 10.1093/molbev/msab029
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide Selection Promotes Antibiotic Resistance in Soil Microbiomes

Abstract: Herbicides are one of the most widely used chemicals in agriculture. While they are known to be harmful to non-target organisms, the effects of herbicides on the composition and functioning of soil microbial communities remain unclear. Here we show that application of three widely used herbicides—glyphosate, glufosinate and dicamba—increase the prevalence of antibiotic resistance genes (ARGs) and mobile genetic elements (MGEs) in soil microbiomes without clear changes in the abundance, diversity and compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 72 publications
5
56
0
Order By: Relevance
“…For example, the surfactant polyethoxylenamine (POEA) has produced negative effects on Vibrio fischeri at lower doses than glyphosate acid [29]. However, given that our results are in general agreement with previous soil experiments using pure glyphosate [23], we believe that our findings are at least in part attributable to an effect of glyphosate itself. Furthermore, regardless of whether it is glyphosate or other constituents of GBH that drive cross-selection of ARGs, assessing the risks associated with commercial formulations is more ecologically realistically, as these formulations are used in agriculture fields and lawns [30].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…For example, the surfactant polyethoxylenamine (POEA) has produced negative effects on Vibrio fischeri at lower doses than glyphosate acid [29]. However, given that our results are in general agreement with previous soil experiments using pure glyphosate [23], we believe that our findings are at least in part attributable to an effect of glyphosate itself. Furthermore, regardless of whether it is glyphosate or other constituents of GBH that drive cross-selection of ARGs, assessing the risks associated with commercial formulations is more ecologically realistically, as these formulations are used in agriculture fields and lawns [30].…”
Section: Discussionsupporting
confidence: 85%
“…An association between glyphosate and increases in ARGs and mobile genetic elements has been previously found in soil microbiomes, as demonstrated in a recent study combining experimental microcosms and environmental data from agricultural field sites in China [23]. Through laboratory assays in three bacterial strains, the authors quantified the conjugation frequency of a multidrug resistance plasmid induced by glyphosate and further investigated changes in cell membrane permeability.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Bacterial composition in soil changes over time with herbicide exposure, with the type of herbicide also affecting composition (Moretto et al, 2017). Glyphosate, glufosinate, and dicamba have increased the occurrence of antibiotic resistance genes and mobile genetic elements in soil microbial communities (Liao et al, 2021). Transfer of these genes between bacteria was also found, whereby herbicides increased conjugation of multidrug resistance plasmids (Liao et al, 2021).…”
Section: Other Challengesmentioning
confidence: 99%
“…Recently, it has been observed that the application of glyphosate increases the prevalence of antibiotic resistance genes in soil microbiomes (Liao et al, 2021). However, this phenomenon seems to be due to an enrichment of antibiotic resistance genes and not caused by a genome-wide glyphosate-induced increase in the mutation rate (Tincher et al, 2017;Liao et al, 2021). Although glyphosate is considered toxicologically safe for animals and humans (Li and Long, 1988), the scientific debate about the toxicity of the weedkiller glyphosate is still ongoing (Arj o et al, 2013;Klingelhöfer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%